The Influence of Financial Ratios to Predict Profit Growth at the Company's Manufacturing Sector Industry Goods Consumption Listed in BEI Period 2014-2016 - Nika Arvina, Kartika Hendra Titisari & Yuli Chomsatu (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
The purpose of this research is to test and analyze the influence of the financialratios as measured by the Current Ratio (CR), Debt to Equity Ratio (DER), TotalAssets Turnover (TATO), Return On Assets (ROA) of profit growth inmanufacturing company the sector industrial of goods consumption listed in BEIperiod 2014-2016. The population in this research is the whole companiesmanufacturing sector industrial goods consumption listed in BEI period 2014-2016. While the method of sampling using a Purposive sampling. The sample usedas many as 20 companies manufacturing sector industrial goods consumptionlisted in BEI period 2014-2016. Methods of data analysis used was multiple linearregression analysis. Method of data analysis in this study uses the help of SPSS 17.The results showed that the variable CR, TATO and ROA effect on profit growth.While variable DER has no effect against the profit growth.Keywords: Profit Growth, Current Ratio (CR), Debt to Equity Ratio (DER), Total AssetsTurnover (TATO), and Return On Assets (ROA).